Solve for o w=fdcos(o)

Math
w=fdcos(o)
Rewrite the equation as fdcos(o)=w.
fdcos(o)=w
Divide each term by fd and simplify.
Tap for more steps…
Divide each term in fdcos(o)=w by fd.
fdcos(o)fd=wfd
Simplify the left side of the equation by cancelling the common factors.
Tap for more steps…
Cancel the common factor of f.
Tap for more steps…
Cancel the common factor.
fdcos(o)fd=wfd
Rewrite the expression.
dcos(o)d=wfd
dcos(o)d=wfd
Cancel the common factor of d.
Tap for more steps…
Cancel the common factor.
dcos(o)d=wfd
Divide cos(o) by 1.
cos(o)=wfd
cos(o)=wfd
cos(o)=wfd
cos(o)=wfd
Take the inverse cosine of both sides of the equation to extract o from inside the cosine.
o=arccos(wfd)
Solve for o w=fdcos(o)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top